Nursing care aimed at the comfort of cancer patients in palliative care (Research, Society and Development, 2023)
The objective was to investigate the nursing care directed to the comfort of the cancer client in palliative care. An integrative review was carried out using the PICo strategy, whose guiding question was “Which nursing care is aimed at the comfort of cancer patients in palliative care? The databases were Scopus and Web of Science. Nine articles published between 2018 and 2021 were identified. The identified nursing care was classified into physical, emotional, spiritual and communicational comfort. Although nursing care still has physical comfort, there is a growing concern to meet all the patient's needs with the objective of offering comfort in an integral way, also valuing emotional, spiritual and communicational support. As a result, nurses have increasingly used non-pharmacological measures to complement care, such as a qigong program, body awareness training, relaxation, massage, guided imagery techniques, psychoeducation, verbal and non-verbal communication strategies. verbal, and facilitation of spiritual practices to assist all needs and promote integral comfort.